Reproductive Biology of Mystus nigriceps from the Tarai River, Kampar Regency, Riau Province - Nataliska Nataliska; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMystus nigricepscommonly inhabit the Tarai River that has been polluted  and it may affects the reproductive biology of the fish. A study aims to understand the reproductive biology of M. nigriceps has been conducted. The fish was sampled        5 times, once/two weeks, from April to July 2019. Parameters measured were Sex Ratio, Gonad maturity Level, Gonad Somatic Index (GSI), fecundity and egg diameter. Results shown that there were 34 males and 66 females (sex ratio 1:2). Male fish was indicated by the presence  of white spot in  tail and it has pointed genital papilla.  The  genital papilla of female is blunt. The size of male ranged from 73.01-140.22 mm (SL), while that of the female ranged from 59.67-160.21 mm (SL). The GSI of male ranged from 0.12 to 13.06%, while that of the female was 0.33-15.35%. The fecundity was 4.644 to 34.938 eggs/fish and egg diameter was 0.4 to 0.7 mm. The eggs in all size distribute evenly in the ovary and it indicates that this fish is a total spawner.Keywords : Catfish, Sex Ratio, Gonad Somatic Index, Total Spawner